Improving the Early Reading Ability of Children with Down Syndrome Through Contextualized SAS Method - Ulandary, Yury; Rochyadi, Endang (International Conference on Elementary Education, 2021)
The ability to read children with Down Syndrome is relatively lower than that of children in general. This is because in reading there are aspects of thinking such as remembering, understanding, comparing, distinguishing, finding, analyzing, organizing, and applying what is contained in the reading. This is difficult for children with Down Syndrome to do so that in the reading process special methods that are not abstract are needed. The purpose of this study was to improve the pre-reading skills of Down Syndrome children through the contextual SAS (Structural Analytic Synthetic) method. The method used in this study is literature research. Based on the results of studies conducted from relevant theories and sources, it shows that the contextual sentence method provides a great opportunity to improve the beginning reading ability of children with Down Syndrome.